Amine–Borane Complexes: Air‐ and Moisture‐Stable Partners for Palladium‐Catalyzed Borylation of Aryl Bromides and Chlorides. Issue 6 (24th March 2015) - Guerrand, Hélène D. S.; Vaultier, Michel; Pinet, Sandra; Pucheault, Mathieu
Abstract A method for using amine–borane complexes directly in palladium catalyzed borylation has been developed. The reaction proceeds through the sequential formation of a boronium species followed by deprotonation leading to the aminoborane. This reagent is then directly used in the borylation process leading, after work‐up, to various boronic acid derivatives. The reaction was applied to (hetero)aryl triflates, iodides, bromides and chlorides. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>